The Role of Teachers in Digital-Based Thematic Learning at Elementary School - Windri Maryana; Adolph Ian A. Dela Torre (Elementary Education Journal, 2021)
Background: This study aimed to describe the (1)  implementation of digital-based thematic learning activities at SD IT Nur Hidayah Surakarta, (2) role of the teacher in the thematic learning activities carried out digitally at SD IT Nur Hidayak Surakarta, and (3) Factors that are driving and inhibiting the implementation of digital-based thematic learning activities. Method: This is qualitative research with a qualitative descriptive design. The subjects in this study were principals, teachers, and students in grades II and IV. The data collection techniques used were interviews, observation, and documentation. The research used primary and secondary data. To determine the validity of the data, the researchers used triangulation of sources and techniques. Result: The results showed that: (1) learning activities at SD IT Nur Hidayah Surakarta class II and IV were carried out online, while still applying a scientific approach to provide meaningful learning to students implementing learning activities applications such as Whatsapp, zoom meeting, and google drive, (2) Teachers have an essential role in the learning activities carried out, being educators, teachers, facilitators, services, designers, managers, assessors, example, and reformer in providing learning modules to help students learn through PowerPoint and videos, (3) The driving factors for the implementation of digital learning activities were the cooperation of all schools, wifi for teachers, training for teachers, flash drives for students, textbooks, modules, availability of devices while the inhibiting factors were wifi limitations, signal difficulties, and device limitations.